Literary criticism of N.A. Otsup in the work "Link" by G.V. Adamovich (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Adamovich wrote articles about Otsup oftenly. Author looked at his compositions, poems and other lirycs. He discovered Otsup's creative methods. Adamovich saw in his creation similar to him features. Both critic and poet were acmeist. They both were very similar in their creation. Critic highly graduated lirics of poet, called simplicity, clarity, masculinity and candor as main features of his creations.
Keywords: acmeism; critics; lyrics; method; reception; article